STRATEGI PENGELOLAAN SUMBER DAYA MANUSIA MAHASISWA UNTUK MENINGKATKAN KESIAPAN KERJA DI UNIVERSITAS WIRABHAKTI MAKASSAR - Kamaruddin Kamaruddin (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
This study aims to analyze student human resource management strategies in enhancing work readiness at Universitas Wirabhakti Makassar. Graduate work readiness has become a critical issue due to the gap between graduates’ competencies and labor market demands. This research employed a qualitative approach with a case study design. Data were collected through semi-structured interviews, observations, and documentation involving ten participants consisting of university leaders, lecturers, student affairs administrators, alumni, and final-year students selected using purposive sampling. Data were analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The findings reveal four main themes influencing students’ work readiness: soft skills development, work experience through internships and field practice, supportive academic environments, and collaboration between universities and industry. These findings indicate that integrated student management strategies contribute significantly to improving graduates’ work readiness. The study provides practical implications for higher education institutions in developing adaptive student development strategies aligned with labor market needs and suggests further research across broader institutional contexts.